Essays on the economics of child labor and fertility - Bruhns, Ramona (2006)
This dissertation analyses the economic development of societies in which parents decide about not only education but also fertility. The parents' decisions are motivated by both financial and altruistic reasons. We focus on human capital formation and population growth as the determinants of economic development, and find that multiple steady-states can exist. In the first two chapters, the focus of the analysis is on the effects of fiscal interventions on both the household decisions and the dynamic of the system. In the third chapter, we examine the households' reaction to mortality shocks such as the HIV/AIDS epidemic, and their long-run economic effects when certain government interventions are financed from sources outside the system.
Keywords: Hochschulschrift; Wirtschaftsentwicklung; Geburtenziffer; Kinderarbeit